Кинетические характеристики пиролиза биомассы - Табакаев Р. Б. Роман Борисович; Алтынбаева Д. Б. Дарига Бахитжановна; Ибраева К. Т. Канипа Талгатовна; Заворин А. С. Александр Сергеевич (2020, 2020)
Заглавие с титульного листа